Hubungan Antara Motivasi Dan Prestasi Belajar Peserta Didik Kelas V Di SDI Onekore 5 Kabupaten Ende - Siprianus See (Ekspektasi: Jurnal Pendidikan Ekonomi, 2022)
The formulation of the problem in this study is What is the relationship between motivation and learning achievements of class V learners at SDI Onekore 5 Ende Regency? The goal to be achieved is to find out the level of relationship between motivation and learning achievements of students of class V SDI Onekore 5. Respondents in this study were class V SDI Onekore 5 learners who numbered 31 people. The research method used is quantitative type exposfacto. Data collection techniques use questionnaires and are supported by documentation and observation. The hypothesis test uses the product moment correlation formula and continues with a simple regression. The results showed that there was a positive and significant relationship between motivation and learning achievement as evidenced by the correlation coefficient value of 0.481 and the probability of 0.001<0.005, and the coefficient of motivational determination to learning achievement of 0.232 or 23.2%. Thus it can be concluded that motivation has a strong enough relationship with the learning achievements of class V learners at SDI Onekore 5. So it needs to be recommended that the school in this case through teachers to further strive to increase the motivation of students through learning in school, while for students to continue to increase their motivation in terms of learning in order to obtain better achievements.